Anti epidermal growth factor receptor therapy in small bowel adenocarcinoma: Case report and literature review. Issue 3 (January 2018) - Falcone, Rosa; Roberto, Michela; Filetti, Marco; Anselmi, Elisabetta; Marchetti, Paolo
Abstract: Rationale: Small bowel adenocarcinoma (SBA) is an uncommon gastrointestinal cancer, thus limited data about treatment for advanced disease are available. The lack of specific guidelines has justified the use of therapeutic protocols usually applied in advanced colorectal cancer. Few and preliminary data have suggested possible clinical benefit from the use of target therapy such as bevacizumab and cetuximab. Patient concerns: We present the case of a young woman who was admitted to the emergency department for acute abdominal pain, nausea, and vomiting related to a jejunal stenosis. Diagnoses: An enteroscopy with jejunal biopsy showed poorly differentiated cancerous cells suggestive for primary intestinal cancer. There were no signs of metastatic disease at radiological evaluation. A jejunal resection was subsequently carried out and the diagnosis of mucinous adenocarcinoma of the jejunum was confirmed. Interventions: The computed tomography scan performed 1 month after surgery showed metastatic disease. Therefore, the patient received combined protocols of chemotherapy and either bevacizumab or the anti-epidermal growth factor receptor (EGFR) panitumumab. Outcomes: A partial response (PR) was achieved with Folfox plus panitumumab and a maintenance therapy with panitumumab is being conducted with a mild toxicity and a progression free survival of 19 months since the beginning of panitumumab. Lessons: This is, to the best of our knowledge, the first report in the literature of a patient with SBA who has benefitted from panitumumab with an overall survival of 83 months.